(untitled) (Journal of the College of Basic Education, 2025)
A Strategic Impact Plan for Learning (KWL) in Learning Some Basic Handball Skills Preparing the modern educational philosophy to use language diversity for effective learning, self-activity for learning, competence, and basic and realistic experiences that you can access so that you can reach learners.The importance of scientific research lies in a different attempt in the field of teaching to advance scientific research techniques and employ these options in learning some work skills.The objectives of the research are summarized in identifying the impact of using the KWL strategy in learning some handball skills. Experimental models were used that were appropriate to the nature of the research problem.The research creativity was represented by first-year students in the Department of Physical Education. They were selected by lottery. The direct sample was represented by Class (1) to represent the experimental group, numbering (20) students, and Class (2), numbering (20) students, to represent the control group.The distinguished results of the experimental group over the control group, which learned traditionally, were in terms of knowledge of some handball skills. Among the influences that the researcher reached, the KWL learning schedule must be used in learning some handball skills. Skills were not used. Creativity in learning schedule (kwL) in physical education lessons in the intermediate stage.